2021
DOI: 10.3389/fimmu.2021.730672
|View full text |Cite
|
Sign up to set email alerts
|

Production of IL-6 and Phagocytosis Are the Most Resilient Immune Functions in Metabolically Compromised Human Monocytes

Abstract: At sites of inflammation, monocytes carry out specific immune functions while facing challenging metabolic restrictions. Here, we investigated the potential of human monocytes to adapt to conditions of gradually inhibited oxidative phosphorylation (OXPHOS) under glucose free conditions. We used myxothiazol, an inhibitor of mitochondrial respiration, to adjust two different levels of decreased mitochondrial ATP production. At these levels, and compared to uninhibited OXPHOS, we assessed phagocytosis, production… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…Our results indicate that primary human skin MCs are different from other types of MCs and cell lines in several aspects. First, we found that the OCR of human skin MCs was about half as high as others have found for BMMCs [ 21 , 27 ], but at the same level as human monocytes and twice as high as that of human CD4+ T-cells, as shown by our recent work [ 28 , 29 ]. It can be assumed that OCR levels may be associated with the cell population size and mitochondrial content.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results indicate that primary human skin MCs are different from other types of MCs and cell lines in several aspects. First, we found that the OCR of human skin MCs was about half as high as others have found for BMMCs [ 21 , 27 ], but at the same level as human monocytes and twice as high as that of human CD4+ T-cells, as shown by our recent work [ 28 , 29 ]. It can be assumed that OCR levels may be associated with the cell population size and mitochondrial content.…”
Section: Discussionsupporting
confidence: 80%
“…Human skin MCs were incubated in a glucose-free RPMI medium in the presence of myxothiazol or rotenone. Afterward, cells were stained with DAPI (BD Pharmingen, catalogue number 559,925, dilution 1:20) according to the manufacturer’s instructions and as recently described [ 28 ]. Data were acquired using a BD FACS Canto™ II (BD Biosciences, San Jose, CA, USA) and processed by FlowJo v7.6.5 (BD Biosciences, San Jose, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Our exploratory evaluation of the mitochondrial metabolism showed a tendency of AH to increase basal mitochondrial metabolism, seemingly linked to energetic request, ATP production being necessary to support phagocytosis and cytokine production, as recently described 59 . It also showed that AH and vaccine impaired both the maximal respiratory capacity of mitochondria, probably in accordance with increasing proton leak, and spare respiratory capacity assessing mitochondrial reserve.…”
Section: Discussionsupporting
confidence: 66%
“…This could be a mechanism of adaptation to the metabolically challenging environment. Such compensatory mechanisms have already been described in monocytes, in which IL6 production is quickly restored after depriving monocytes of ATP and glucose ( 13 ).…”
Section: Discussionmentioning
confidence: 69%